The effect of dialysis type on left atrial functions in patients with end‐stage renal failure: A propensity score‐matched analysis. Issue 3 (11th December 2017) - Aksu, Uğur; Aksu, Derya; Gulcu, Oktay; Kalkan, Kamuran; Topcu, Selim; Aksakal, Enbiya; Aksakal, Emrah; Sevimli, Serdar; Tanboga, Ibrahim Halil
Abstract : Introduction: Despite the widespread use of both hemodialysis (HD) and peritoneal dialysis (PD), there is no study comparing the effects of these dialysis methods on the left atrial (LA) volume and functions. In this study, we investigated the impact of different dialysis methods on the LA volume and function in the patients exposed to chronic pressure overload and volume overload. Method: This study was carried out on the patients who received dialysis treatment at our healthcare center between March, 2015 and January, 2016. Twenty‐eight patients receiving hemodialysis (HD) treatment and 24 patients under PD treatment were enrolled into the study. Patients were divided into 2 groups according to the dialysis therapy, and the atrial volumetric and mechanical functions were investigated. Results: As the basal demographical characteristics of patients in the PD and HD groups were significantly different, 44 patients matched on a 1:1 basis were taken for final analysis (22 HD, 22 PD, and the average age of 42.4 ± 4.8; 73% was male). After propensity score matching analysis, it was determined that left atrial volume index (LAVi) was higher in the HD group while peak LA strain and LA contraction strain were higher in the PD group. Additionally, both strain parameters showed a good negative correlation with LAVi. Conclusion: We demonstrated that the left atrial structure and functions were better in the PD group suggesting that PD may be a relatively better option for the preservation and maintenance of the left atrial functions as compared to HD.